American National Identity in Crèvecoeur’s Letters From an American Farmer Letter Three as a Case Study - Ammari Hanifa Wafa, Benyounes Hana (My University, 2018)
ABSTRACT The present dissertation is intended to examine the theme of American National Identity in Crevecoeur’s Letters from an American Farmer. It aims at providing a historical background about the era in which the work was achieved. It focuses on portraying Crevecoeur’s view of major enlightenment principles. In addition to that, this study reflects a positive image given by the author concerning the new man “American” by tackling the meaning of Personal and National Identity. Throughout the letters, the sense of nationalism for European Countries had disappeared, so American Nationalism as a concept is discussed as well as in this work. Moreover, a deep analysis is given to the third letter “What is an American”, all the way through giving much importance to how American National Identity was built in the new found land by applying New Historicism theory. In order to find answers to the proposed research questions, Historical and Analytical approaches are to be used. The result of this study shows that John de Crevecoeur’s third letter is a true representation of the reflection of the American Enlightenment basis: Deism, liberation, republicanism and toleration. As a writer, Crevecoeur really succeeded in his presentation of depicting American National Identity along with Nationalism during the Enlightenment era. Besides, the research proves that Crevecoeur celebrates the perfection of America.